Picosecond photoluminescence intensity correlation measurements of hot carriers in GaAs/AlxGa1-xAs quantum wells - de Paula, A; Ryan, J; Eakin, H; Tatham, M; Taylor, R; Turberfield, A (Elsevier, 1994)
We have measured the energy relaxation of hot carriers in doped and undoped GaAs/AlxGa1-xAs quantum wells by detecting time-resolved hot luminescence using a two-pulse intensity correlation technique. The results are compared with time-dependent intensity correlation functions calculated using a model of energy relaxation by optical phonon interactions which includes non-equilibrium phonon effects. The excellent agreement between calculated and experimental correlation functions shows the great potential of this method in measuring ultrafast relaxation processes.